MADRASAH SEBAGAI PENDIDIKAN ISLAM UNGGUL - Mahfud Ifendi (Institut Keislaman Abdullah Faqih (INKAFA) Gresik, 2017)
This article describe madrasah which becomes kind of Islamic educational institution in Indonesia, and it’s existence is an alternative answer in today’s modern era, the idea of modernization and giving religious value become the hallmark of madrasah as a superior education in Indonesia. In additional curriculum modification which developed by madrasah are able to balance between world affairs with the matter of after-life. A worthy effort which should always be appreciated for madrasah is the spirit to educate the nations, especially Muslim community which has limited cost. The expectation that never be lost in this madrasah mission is to be a superior educational institution and gain the trust of the wider community.Keywords: Madrasah, Islamic educational, Excellence.